Sedentary Lifestyle dan Metabolic Syndrome sebagai Predictor Kejadian Sindrom Koroner Akut pada Dewasa Muda - Rai Bawa, Ngakan Nyoman; Nurachmah, Elly; Adam, Muhamad; Maria, Riri (Journal of Telenursing (JOTING), 2024)
The aim of this study is to identify Sedentary Lifestyle and Metabolic Syndrome as predictors of the incidence of Acute Coronary Syndrome. The method used in this research was the PRISMA (Preferred Reporting Items for Systematic-Reviews and Meta-Analyses) search strategy. The databases used in the literature search were Clinical Key Nursing, ScienceDirect, Springer link, Proquest, EBSCOHost. The results of the study show that there are two groups of predictors in the literature search that cause Acute Coronary Syndrome in young adults. Conclusions based on the 7 articles analyzed in the study showed that Sedentary Lifestyle and Metabolic Syndrome were the main risk factors determining the incidence of Acute Coronary Syndrome in young adults. Keywords: Metabolic Syndrome, Predictor, Sedentary Lifestyle, Acute Coronary Syndrome